Differences between clicker and voice when used as event markers in shaping novel behaviors in dog training - González Ramírez, Mónica Teresa; Landero Hernández, René; Vanegas Farfano, Minerva (Universidad Pontificia Bolivariana, Facultad de Psicología, 2017)
Abstract The principles of operant conditioning are often applied in canine training. Their correct application requires a good timing, well-defined criteria and a proper rate of reinforcement. Few studies have compared the types of markers of canine training events; the most used are the clicker and the voice. Objective: to compare the number of reinforcers required to shape seven new behaviors in two canine subjects, contrasting the use of the clicker and the voice as markers of events. Results: there is evidence of equivalence in the number of reinforcers needed to achieve the behavior to shape with the use of the clicker and the use of the voice. Conclusions: at least in this study, the timing and the shaping are not affected by the type of marker of events used.